Synthesis and characterization of poly(propylene glycol) polytrioxamide and poly(urea oxamide) segmented copolymers. Issue 7 (21st December 2013) - Buckwalter, Daniel J; Hudson, Amanda G; Moore, Robert B; Long, Timothy E
Abstract This report describes the synthesis and characterization of unprecedented poly(propylene glycol) (PPG) polytrioxamide and poly(urea oxamide) (UOx) segmented copolymers containing monodisperse hard segments. Synthesis of the segmented copolymers relied on an efficient two‐step end‐capping sequence, which resulted in novel difunctional oxamic hydrazide‐terminated polyether oligomers. Polymerization with oxalyl chloride or 4, 4′‐methylenebis(cyclohexyl isocyanate) provided the desired segmented copolymers displaying thermoplastic elastomeric behavior. Variable‐temperature Fourier transform infrared and 1H NMR spectroscopies confirmed the presence of hard segment structures and revealed ordered hydrogen bonding interactions with thermal dissociation profiles similar to those of polyurea and polyoxamide copolymer analogs. Dynamic mechanical analysis of PPG‐UOx exhibited a longer, rubbery plateau with increased moduli compared to PPG polyurea, and tensile analysis revealed a dramatic increase in copolymer toughness due to enhanced hydrogen bonding. A new step‐growth polymerization strategy is described that is capable of producing tunable hydrogen bonding segmented copolymer architectures. © 2013 Society of Chemical Industry